Isolasi Enterobacteriaceae Patogen dari Makanan Berbumbu dan Tidak Berbumbu Kunyit (Curcuma longa L.) Serta Uji Pengaruh Ekstrak Kunyit (Curcuma longa L.) Terhadap Pertumbuhan Bakteri Yang Diisolasi - Ernin Hidayati; Nuryati Juli; Erly Marwani (Jurnal Matematika & Sains, 2002)
An isolation of pathogenic Enterobacteriaceae bacteria has been done on spiced foods with turmeric and without turmeric ingredients. Food samples were taken randomly from 8 traditional food vendors at a traditional market in north Bandung during three seasons for 6 months. Next step was extraction of turmeric rhizome with sequential extraction method using n-hexane, ethyl acetate and ethanol. Those extracs were applied onto 4 chosen bacterial isolates using Kirby Bauer method, cylinder/hole plate method, and dilution method. There were 8 bacterial isolates which always present in all season. Also there were 4 isolates only found in rainy season. Eight isolates among them were pathogens. Total frequency of bacteria in samples with turmeric ingredients was lower than that without turmeric ingredients. The effect of extracts on all tested bacteria (Escherchia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus), showed that n-hexane extract could inhibit the growth of Escherchia coli, Klebsiella pneumoniae and Staphylococcus aureus at concentration of 50.000 ppm on solid medium. However in liquid medium, all tested bacteria were inhibited at the concentration of 1000 ppm.